Macronutrient and mineral contents of five local black rice (Oryza sativa) cultivars in Indonesia - Muh Nashrurrokhman; Puspa Restu Sayekti; Ayu Safitri; Yekti Asih Purwestri; Rarastoeti Pratiwi (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Nashrurrokhman M, Sayekti PR, Safitri A, Purwestri YA, Pratiwi R. 2019. Macronutrient and mineral contents of five local black rice (Oryza sativa) cultivars in Indonesia. Biodiversitas 20: 3647-3653. Nutrient composition is important information that can be used to support the development of black rice as functional food. In this study, the macronutrient and mineral compositions of five black rice cultivars were determined by measuring the contents of total carbohydrates, proteins, and lipids, and levels of the minerals Ca, Fe, and Zn of whole rice, refined rice, and rice bran. Rice samples were obtained from farmers who planted the black rice cultivars of Woja Laka, Toraja, Cempo Ireng “Seyegan”, Melik “Bantul” and Wedomartani. Proximate analysis and spectrophotometric methods were performed to measure the contents of macronutrients and minerals. Statistical analysis of all quantitative data was conducted by using One-way analysis of variance (ANOVA) (p<0.05) using the SPSS-25 program. Results showed that the contents of carbohydrates, proteins, and lipids in the five rice cultivars varied in the range of 61.80%-65.58%, 7.13%-9.10%, and 1.98%-3.23%, respectively. Carbohydrates found in refined rice were in the range of 62.71%-67.89%, while rice bran had protein and lipid contents varying in the range of 10.95%-11.48% and 5.70%-6.86%, respectively. Rice bran also had the highest mineral content and the highest mineral content was 30 ?g/g Ca compared to Fe and Zn. Therefore, the macronutrient and mineral composition varied among the five black rice cultivars and rice components. The highest carbohydrate content was found in refined rice, while the highest proteins, lipids, and minerals (Ca, Fe, and Zn) contents were found in rice bran.